On the Deposition Rates of Magnetron Sputtered Thin Films at Oblique Angles. Issue 6 (17th April 2014) - Alvarez, Rafael; Garcia‐Martin, Jose M.; Lopez‐Santos, Maria C.; Rico, Victor; Ferrer, Francisco J.; Cotrino, Jose; Gonzalez‐Elipe, Agustin R.; Palmero, Alberto
Abstract We describe here the deposition of thin films using magnetron sputtering at oblique angles. General relations between the deposition rates of the films and experimental parameters, such as gas pressure or substrate tilt angles, are deduced and experimentally tested. The model also permits the direct determination of the thermalization mean free path of the sputtered particles in the plasma gas, a key parameter defining the balance between ballistic and diffusive flows in the deposition reactor. The good agreement between experimental and calculated results supports the validity of our description, which becomes a useful tool to explain the main features of the magnetron sputtering deposition of thin films at oblique angles.<inline-graphic xlink:href="ark:/27927/pghmhk0phn" content-type="ppap201300201-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />